Factors Related to Compliance of ARV Medication in HIV Patients at RSCM Jakarta - Chryest Debby; Sondang Ratnauli Sianturi; Wilhelmus Hary Susilo (Jurnal Keperawatan, 2019)
Antiretroviral therapy is believed not to be able to cure the disease; however, it can reduce mortality and morbidity. It also improves the quality of life of people with HIV. The success of the HIV/AIDS treatment is determined by adherence to antiretroviral therapy. ARV therapy is given in a long run and can be said as optimal if the compliance reaches more than 95%. The purpose of this study was to determine the relationship between certain factors and adherence to ARV therapy in people with HIV/AIDS. The design of this study was a descriptive correlational study with a cross-sectional approach. A total of 198 patients were recruited through a purposive sampling technique. The result of the study showed that there was no relation between adherence with age (p-value of 0.327), education (p-value of 0.859), and treatment (p-value of 0.74). From this study, it can be recommended that nurses need to improve their HIV counseling skills, especially about the benefits of adherence using a communicative media. Hospitals should also encourage more support to achieve better adherence in patients living with HIV/AIDS. Keyword: Adherence, HIV/AIDS, Antiretroviral Therapy